Analysis of the Influence of Social Interaction and Organizational Culture on the Optimism of Elementary School Educators in Pangean District - Musriadi Musriadi; Bunari Bunari; Daeng Ayub (Jurnal Ilmiah Global Education, 2026)
The purpose of this study was to investigate how social interaction and organizational culture impact the optimism of elementary school teachers in Pangean district. Teacher optimism is an essential psychological resource that determines mental resilience, motivation, and performance quality. This study used a quantitative approach with an ex post facto design. The study population consisted of 202 teachers from 19 public elementary schools, and a sample of 135 teachers was obtained using the Taro Yamane formula, with random selection based on clusters. Primary data collection was conducted using a structured questionnaire, developed based on a five-point Likert scale, which underwent validity and reliability tests. Data interpretation was carried out using simple and multiple regression, as well as t-tests, F-tests, and the coefficient of determination (R²). The results showed that social interaction had a positive and significant influence on teacher optimism, with a contribution of 41.2%. Organizational culture also had a positive and significant impact, with a contribution of 42.7%. Together, these two variables contributed 42.7% of teacher optimism, with an R of 0.653, indicating a significant correlation, and a Sig. value. The F-value was 0.000, validating the model's significance. These findings indicate that good social relationships and a supportive organizational culture are crucial for teachers to have a more positive outlook on their profession. This study confirms that the growth of optimism among teachers depends on the support of a positive social environment and a strong organizational culture. Therefore, schools and educational policymakers need to improve collaborative, communicative, and emotionally welcoming environments for teachers